Penerapan Konsep Finite State Automata Dalam Proses Pendaftaran Kelas Kursus Bahasa Inggris Pada Tempat Kursus - Aziz, Faruq; Said, Fadillah; Sudrajat, Adjat (MATICS, 2020)
Research on website-based test applications for digital course registration in order to make it easier for course institutions to determine classes that are consistent and effective and efficient. This research provides alternative solutions for course institutions for class selection or course program that is suitable for users who will study at the place of the course which is cost-effective and time-consuming too. In this study a course registration application is designed by integrating a website and database to retrieve data after the user has tested. It is intended that users who want to learn English can receive a choice of classes or programs in accordance with their abilities and initial knowledge. This minimizing test instructor errors in determining class and program choices that will be obtained by the user. In this study using the Finite State Automata (FSA) method to discuss the NFA type FSA model can be implemented in the registration process to the user (member) where the course is expected as needed and can better understand how the process of class or program selection is effective and right on target